An oil/water separation nanofibrous membrane with a 3-D structure from the blending of PES and SPEEK. (June 2019) - Du, Qiong; Chen, Zheng; Jiang, Xiangyu; Pang, Jinhui; Jiang, Zhenhua; Luan, Jiashuang
A new nanofibrous membrane (NFM) was prepared by blending polyethersulfone (PES) and sulfonated poly(ether ether ketone) (SPEEK) via electrospinning. The membrane exhibits good thermal stability and high mechanical strength. The hydrophilicity of the membrane could be controlled by adjusting the mass ratio of PES to SPEEK. PES acts as the backbone fiber and provides high mechanical strength, while SPEEK provides hydrophilic functional groups due to the strong hydrophilicity of the sulfonic group. The test results show that the composite NFM integrates the advantages of the two polymers. Simple adjustment of the weight ratios of the two polymers can enable an adjustable flux so that the membrane can be used for different kinds of oil/water separation. The results show that NFMs can not only separate immiscible oil/water systems but also separate oil-in-water emulsions. The immiscible oil/water separation process was driven only by gravity and had a high flux of 1119.63 Lm −2 h −1 . This separation process conserves energy, which is beneficial for environmental protection. The separation flux of the oil-in-water emulsion was 758.71 Lm −2 h −1 bar −1 based on measurements under different pressures, and the separation purity total organic carbon was below 50 ppm. This work indicates that a membrane comprised of PES and SPEEK has excellent performance and can be used in different fields.